Italy : 2022 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Italy. (IMF Staff Country Reports; Country Report, 2022)
GDP has fully recovered from the pandemic crisis, but government debt has risen to very high levels. The war in Ukraine triggered a surge in energy prices and the prospect of monetary policy tightening caused government bond yields to rise sharply. Implementation of the National Recovery and Resilience Plan (NRRP), which provides large EU grants and loans conditioned on implementing a comprehensive reform and investment program, is underway.